Ozonation Pretreatment Evaluation for Xylanase Crude Extract Production from Corncob under Solid-State Fermentation - Efri Mardawati; Surya Martha Pratiwi; Robi Andoyo; Tita Rialita; Mochamad Djali; Yana Cahyana; Een Sukarminah; In-In Hanidah; Imas Siti Setiasih (Journal of Industrial and Information Technology in Agriculture, 2017)
Xylanases are highly exploited enzyme in industries, including food and chemical industry. Xylanases can be utilized in catalyzing the endohydrolysis of 1,4-β-xylosidic linkages in xylan, lignocellulosic component to produce xylose-monomer. This research aims to optimize xylanase production from alternative substrate, corncob. Corncob contains 41.17% of hemicellulose, polymer of xylan. Xylanases are produced through solid state fermentation by Trichoderma viride. Ratio between substrate and moistening solution was 0.63 g/mL with fermentation temperature 32,8OC. Variables varied include incubation time and pretreatment (using autoclave, ozonation, combination of ozonation and autoclave, also without pretreatment). Xylanase activity was measured by DNS method using 1% of xylan as substrate standard. The result showed that the best incubation time is 36 h with 14403.8707 U/mg protein for specific xylanase activity by using autoclave as pretreatment.  Ozonation pretreatment process can increase the enzyme activity of xylanase.